Pengabdian Masyarakat Berbasis Teori Organisasi: Strategi Penguatan - Andry Eryanto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Community service is one of the main pillars of the Tridharma of higher education which aims to apply knowledge to solve various social problems. This article examines the strategy of strengthening community institutional capacity based on organizational theory as a systematic, contextual, and sustainable approach. By using a participatory-collaborative approach and a framework of organizational theory, open systems, and contingency theory, community service activities are designed to strengthen the internal structure, values, and social dynamics of local community institutions. This study shows that an approach based on organizational theory can improve the ability of institutions to adapt to external changes, manage resources, and establish strategic networks. The results of the institutional capacity strengthening process include increased managerial competence, local leadership, participatory governance, and organizational sustainability. These findings are in line with the sustainable development goals (SDGs), especially in the aspect of inclusive and accountable institutions. Thus, community service based on organizational theory is a relevant intervention model for building an independent, adaptive, and resilient society.